Pengaruh Harga, Electronic Word of Mouth, dan Celebrity Endorser terhadap Purchase Decision pada Distro CRSL di Yogyakarta - Alfiana Isnaini; Ralina Transistari; Ilman Taufiq Lazuardy (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This research aims to determine the influence of price, electronic word of mouth, and celebrity endorsers on purchase decisions at CRSL distribution in Yogyakarta. This type of research is descriptive quantitative research with a non-probability sampling method and the sampling technique using purposive sampling. This research involves 100 respondents from the entire population of CRSL consumers in Yogyakarta. Data analysis tool using SPSS version 26. The results of this study indicate that price does not affect purchase decisions, while electronic word of mouth and celebrity endorsers have a positive influence on purchase decisions at CRSL distro in Yogyakarta.